Transformasi pembelajaran bahasa di era kecerdasan buatan: Tinjauan cakupan menuju pencapaian SDGs - Ren Sherlaine B. Sombilon; Aisyah Puan Maharani; Ana Mae M. Monteza; Muhammad Wazid Husni (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2025)
This study of AI integration into language learning is a literature review research design that focuses on understanding the different aspects of AI integration into language learning. It investigates AI’s potential to enhance language learning, emphasizing advantages and disadvantages. Methodologically, this study utilized a scoping review to collect and analyze secondary data from sixteen qualified articles retrieved from Google Scholar and Scopus databases. AI applications are becoming more common in educational settings, especially in language acquisition, due to the quick advancement of technology. The study highlights the effects of AI on learner engagement, tailored education, and flexible learning solutions by synthesizing findings from studies carried out between 2020 and 2024. The efficiency of chatbots and intelligent tutoring systems, the ethical implications of academic honesty, and the improved social presence of students through AI tools are some of the major themes. AI’s potential benefits, issues, including data privacy, technology accessibility, and teacher preparation requirement,s were also discussed. Aligned with the Sustainable Development Goals (SDGs), particularly SDG 4 (Quality Education) and SDG 10 (Reduced Inequalities), the findings highlight the need for continued study and the creation of AI solutions suited to various learner requirements. This study provides insights that guide future pedagogical approaches and technology advancements, making it a valuable tool for researchers and educators attempting to comprehend the intricate dynamics of AI integration in language learning.